2018
DOI: 10.1007/s40572-018-0192-1
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Arsenic Exposure and Lung Function: Is There Evidence of Restrictive or Obstructive Lung Disease?

Abstract: Purpose of review: Hundreds of millions of people worldwide are exposed to arsenic via contaminated water. The goal of this study was to identify whether arsenic-associated lung function deficits resemble obstructive- or restrictive-like lung disease, in order to help illuminate a mechanistic pathway and identify at-risk populations. Recent findings: We recently published a qualitative systematic review outlining the body of research on arsenic and non-malignant respiratory outcomes. Evidence from several po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 55 publications
(92 reference statements)
3
20
0
Order By: Relevance
“…More recently, water arsenic > 100 μg/L has been associated with non-malignant respiratory effects, including respiratory symptoms and worse lung function tests. A recent meta-analysis identified an association between arsenic exposure and reduced forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1) with a preserved ratio (in subset of 3 studies reporting FEV1/FVC), indicating a possible association with restrictive lung disease [4]. The studies in the meta-analysis included a wide range of exposure levels, with arsenic often 10 times higher than the World Health Organization guideline/United States Environmental Protection Agency standard of 10 μg/L in drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, water arsenic > 100 μg/L has been associated with non-malignant respiratory effects, including respiratory symptoms and worse lung function tests. A recent meta-analysis identified an association between arsenic exposure and reduced forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1) with a preserved ratio (in subset of 3 studies reporting FEV1/FVC), indicating a possible association with restrictive lung disease [4]. The studies in the meta-analysis included a wide range of exposure levels, with arsenic often 10 times higher than the World Health Organization guideline/United States Environmental Protection Agency standard of 10 μg/L in drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…However, even subtoxic doses of arsenic may significantly affect respiratory functions. Particularly, a recent meta-analysis demonstrated that arsenic exposure is associated with restrictive impairments in lung function including reductions in forced expiratory volume in one second (FEV1), forced vital capacity (FVC) ( Sanchez et al, 2018 ). Another study has demonstrated that As-associated FVC reduction is observed on males ( Khan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…2018 ; Moon et al. 2017 ; Sanchez et al. 2018 ), and water contaminant present in many aquifers in the United States.…”
Section: Introductionmentioning
confidence: 99%